A Study of Zero-and first-degree terms in geopotential models over Australia - Kirby, Jonathan; Featherstone, Will (Institution of Surveyors, Australia, 1997)
By virtue of the formulation of the boundary value problem of physical geodesy, the zero and first-degree terms in any gravimetrically determined geoid are omitted. With the advent of space-based positioning, notably GPS, geometrical control is now available with which to constrain these terms. Furthermore, the fit of a geopotential model gravity field to the terrestrial gravity field can also give some indication as to the magnitude of the zero-degree term. This investigation compares a series of global geopotential models with absolute geometrically-determined geoid heights derived from the Australian Fiducial Network and terrestrial gravity anomalies from the Australian gravity data-base in order to deduce the magnitude of these terms in the Australian context.